THE EFFECT OF HEAT TREATMENT AND PRESSING AT 400 °C WITH COCONUT SHELL CHARCOAL MEDIA ON THE HARDNESS, MICROSTRUCTURE, AND DENSITY OF AL-SI ALLOYS - Masyrukan Masyrukan; Agung Setyo Darmawan; Agus Hariyanto; Pramuko Ilmu Purboputro; Hanif Alfian Ihwanudin; Muhammad Ibnu Pamungkas (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine the effect of the heat treatment process and pressing on hardness, density, and morphological changes in the microstructure of Al-Si alloys. In this study, the medium used was coconut shell charcoal with a mesh size of 80 at a heat treatment process of 400 °C and a holding time of 75 minutes. The pressing was carried out with a load of 150 N. The result of this research is an increase in the hardness of the Al-Si alloy with an average value of 133 VHN after the Heat Treatment and pressing process. In the microstructure, there is a morphological change in the Al-Si alloy with the reduction of Si elements and also an increase in the density value after the heat treatment process.